FACTORS CORRELATED TO EARLY BREASTFEEDING INITIATION IN SITI FATIMAH MOTHER AND CHILD REGIONAL SPECIAL HOSPITAL OF MAKASSAR - Nurhikmah Nurhikmah (Stikes Graha Edukasi Makassar, 2019)
Introduction: Early breastfeeding initiation is an opportunity given to infants soon after born by putting them on their mothers' stomach. Then, they are let free for at least the first 60 minutes (1 hour) after born. The purpose of this research is to find out the factors related to the early breastfeeding initiation at the Siti Fatimah Makassar Special District Hospital. Method: The research was a cross sectional study. The populations were post partum mothers in Siti Fatimah Mother and Child Regional Special Hospital of Makassar. The samples were some of the populations selected using systematic random sampling technique. The data were obtained using research instrument. Results: the research indicate that there is a correlation between mothers' knowledge and early breastfeeding initiation with a value of p = 0.000 which means that Ho is rejected and Ha is accepted. There is also a correlation between mothers' attitude and early breastfeeding initiation with a value of p = 0.000 which means that Ho is rejected and Ha is accepted. Besides, there is a correlation between mothers' parity and early breastfeeding initiation with a value of p = 0.000 which means that Ho is rejected and Ha is accepted. Conclusion: Maternal knowledge, maternal attitudes, parity of mothers have corelation with initiation of early breastfeeding.